Modeling an intelligent agent augmented gaming environment - Kumar, Rohit Ashwini. (2011)
The software community is focused on making the computer more sociable, with intelligent games that use autonomous agents. Agents, or computer-generated characters, are an integral part of every software, enhancing the experience of virtual worlds and assisting the users with learning or entertainment. This project looks at two different, yet important techniques in improving the agent modeling.